Monitoring spatiotemporal changes in land use/land cover and its impacts on ecosystem services in southern Zambia - Diling Liang; James Reed; Sima Fakheran; Kaala Moombe; Freddie Siangulube; Terry Sunderland (Environmental Research Communications, 2024)
Ecosystems play a vital role in human well-being, yet the widespread loss of ecosystem services due to human activities, including agricultural expansion and deforestation, remains a significant concern. Despite the wealth of research highlighting the importance of ecosystem conservation in Zambia, a critical gap exists in understanding the interplay between the conservation of ecosystem services and the socio-economic needs of local communities. This study presents a comparative analysis of ecosystem services in two distinct landscapes within southern Zambia: the protected area of Kafue National Park (KNP) and the agricultural landscape of Kalomo district between 2000–2020. Employing a combination of quantitative and qualitative methods, we evaluate the impacts of land/use and land cover (LULC) changes on selected ecosystem services, with a particular focus on carbon storage and the habitat quality of the trumpeter hornbill. The results of the comparison indicate that: (1) the Kalomo district has suffered from extensive land conversion, with forest changing to cropland, while KNP was well protected from encroachment, with forest area increasing over time; (2) carbon stocks and the habitat quality of trumpeter hornbills continually decreased in the Kalomo district but improved in KNP; (3) Kalomo district has suffered rapid environmental degradation due to an imbalance between economic development and environmental conservation, while strict enforcement in KNP has preserved ecosystems. The findings underscore the importance of integrated and inclusive land-use planning and natural resource governance for maintaining and enhancing ecosystem services in Zambia. To progress towards landscape management that is both sustainable and equitable, aligning with the objectives of the Global Biodiversity Framework, it is proposed that a comprehensive approach be adopted in the region. This approach should encompass a more thorough consideration of local livelihood requirements, as well as the wider political-economic and social factors at play.